Academic Retention, Research Capacity, and Sustainable Development in African Universities - Saheed Rufai; Hafsah Olatunji; Bello Musa (Universitas Djuanda, 2021)
There is a shift of interest towards the current pace of development in Africa especially with regard to science and technology. The rate at which advancements are being recorded in this and other sectors has not been encouraging, as evident from official records. Scholars and researchers in various disciplines have correlated development to education and identified close associations between the level of performance of any citizenry or manpower, and the quality of its education. Accordingly, the quality of life and experience on the African continent has, to an appreciable extent, been characterised as the output variable and the quality of education including that of the teachers, as the input variable. The antecedent variable, too, which in this context is the totality of experience that informs educational directions in Africa, is arguably a product of the input variable. Consequently, the tertiary educational level especially the university system, unlike both the primary and the secondary, may be more strongly associated with the quality of performance. This may be explained through the dominant thinking that the tertiary system is primarily concerned with the production of manpower for various sectors. While there is evidence of research into this question, there is insufficient evidence of research into the interplay of the academic retention system and research capacity development orientation in African universities. This paper is an attempt to investigate that hitherto underrepresented dimension. The study employs a combination of the historical method and analytic philosophy. Its significance lies in its potential to expose, with evidence, the association between the dominant academic retention system and research capacity development orientation in African universities, as well as the implication of such an association for sustainable development in Africa. The study ultimately offers an ameliorative proposal for revitalizing an outcome-oriented research capacity development system in African universities.